2011
DOI: 10.1371/journal.pone.0018419
|View full text |Cite
|
Sign up to set email alerts
|

Major Reduction in Anti-Malarial Drug Consumption in Senegal after Nation-Wide Introduction of Malaria Rapid Diagnostic Tests

Abstract: BackgroundWhile WHO recently recommended universal parasitological confirmation of suspected malaria prior to treatment, debate has continued as to whether wide-scale use of rapid diagnostic tests (RDTs) can achieve this goal. Adherence of health service personnel to RDT results has been poor in some settings, with little impact on anti-malarial drug consumption. The Senegal national malaria control programme introduced universal parasite-based diagnosis using malaria RDTs from late 2007 in all public health f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
130
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(140 citation statements)
references
References 22 publications
9
130
0
Order By: Relevance
“…Even when tests are carried out, findings are accumulating from studies in different countries that show between 35 and 85% of RDT negative patients have been prescribed antimalarials Bisoffi et al, 2009;Chinkhumba et al, 2010;Elmardi et al, 2009;Hamer et al, 2007;Kyabayinze et al, 2010;Reyburn et al, 2007;Skarbinski et al, 2009). By contrast, other studies have found a reduction in overdiagnosis, down to between 4% and 16% RDT negative patients receiving antimalarials after the introduction of RDTs with various supporting interventions (Bastiaens et al, 2011;D'Acremont et al, 2009;Hopkins, 2008;Masanja et al, 2010;Mawili-Mboumba et al, 2009;Msellem et al, 2009;Thiam et al, 2011;Williams et al, 2008). In spite of this mixed evidence over the effect of introducing RDTs, and in the absence of good information about the best way to support their introduction for effective adoption, scale-up of the tests is being promoted (World Health Organisation, 2010), and many countries including Cameroon have included the tests in their Global Fund grant applications (Ministry of Public Health, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Even when tests are carried out, findings are accumulating from studies in different countries that show between 35 and 85% of RDT negative patients have been prescribed antimalarials Bisoffi et al, 2009;Chinkhumba et al, 2010;Elmardi et al, 2009;Hamer et al, 2007;Kyabayinze et al, 2010;Reyburn et al, 2007;Skarbinski et al, 2009). By contrast, other studies have found a reduction in overdiagnosis, down to between 4% and 16% RDT negative patients receiving antimalarials after the introduction of RDTs with various supporting interventions (Bastiaens et al, 2011;D'Acremont et al, 2009;Hopkins, 2008;Masanja et al, 2010;Mawili-Mboumba et al, 2009;Msellem et al, 2009;Thiam et al, 2011;Williams et al, 2008). In spite of this mixed evidence over the effect of introducing RDTs, and in the absence of good information about the best way to support their introduction for effective adoption, scale-up of the tests is being promoted (World Health Organisation, 2010), and many countries including Cameroon have included the tests in their Global Fund grant applications (Ministry of Public Health, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…[1][2][3] In Senegal, malaria transmission has declined recently, 4 although Plasmodium falciparum remains endemic throughout the country. 5 Malaria transmission occurs from mosquito to man and from man to mosquito. Transmission from man to mosquitoes is poorly quantified 6 and a focus often lies on entomological parameters like aggressiveness of anophelines to humans, the entomological inoculation rate, vectorial capacity, 7,8 and indicators of parasite prevalence in the human population.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance is occurring as a consequence of several factors, including poor treatment practices, inadequate patient adherence to prescribed antimalarial regimens, widespread availability of artemisininbased monotherapies and substandard forms of the drug [9,10]. In recent years, parasite resistance to artemisinins -the key compounds in artemisinin combination therapy (ACTs) -has been detected in four countries of the Greater Mekong subregion: Cambodia, Myanmar, Thailand and Vietnam in agreement with the prediction of the World Health Organization (WHO) 2010 [6].…”
Section: Introductionmentioning
confidence: 99%